2016
DOI: 10.1210/en.2016-1431
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Stimulation of Kiss1 Expression in the Medial Amygdala Involves Estrogen Receptor-α But Not Estrogen Receptor-β

Abstract: The neuropeptide kisspeptin, encoded by Kiss1, regulates reproduction by stimulating GnRH secretion. Neurons synthesizing kisspeptin are predominantly located in the hypothalamic anteroventral periventricular (AVPV) and arcuate nuclei, but smaller kisspeptin neuronal populations also reside in extrahypothalamic brain regions, such as the medial amygdala (MeA). In adult rodents, estradiol (E) increases Kiss1 expression in the MeA, as in the AVPV. However, unlike AVPV and arcuate nuclei kisspeptin neurons, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…Whether these alterations in LH secretion are also influenced by the massive increase in Kiss1 mRNA expression in extra‐hypothalamic sites, such as the amygdala, BNST and lateral septum that we have previously reported in GABAB1KO mice, and which are also regulated by Esr1 similar to Kiss1 neurones in the AVPV/PeN remains to be determined. Interestingly, Pineda et al have very recently demonstrated that amygdala kisspeptin neurones innervate GnRH neurones in the preoptic area and Adekunbi et al have shown that antagonism of medial amygdala kisspeptin delayed puberty onset, disrupted oestrous cyclicity and reduced the incidence of LH surges, giving support to this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…Whether these alterations in LH secretion are also influenced by the massive increase in Kiss1 mRNA expression in extra‐hypothalamic sites, such as the amygdala, BNST and lateral septum that we have previously reported in GABAB1KO mice, and which are also regulated by Esr1 similar to Kiss1 neurones in the AVPV/PeN remains to be determined. Interestingly, Pineda et al have very recently demonstrated that amygdala kisspeptin neurones innervate GnRH neurones in the preoptic area and Adekunbi et al have shown that antagonism of medial amygdala kisspeptin delayed puberty onset, disrupted oestrous cyclicity and reduced the incidence of LH surges, giving support to this hypothesis.…”
Section: Discussionmentioning
confidence: 95%
“…The kisspeptin receptor, encoded by Kiss1r , was also identified. The kisspeptin system has been studied in the amygdala in the context of estrogen signaling in males (Stephens et al, 2016) and in sexual behavior (Gresham et al, 2016). Another gene, Thra , to our knowledge has not bee studied in the BnST of males, but knockout mice exhibit increased anxiety, as well as facilitated sexual behavior, with decreased mount and intromission latencies (Vasudevan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, if this constitutes a sex difference in the expression of SP or it is a mere reflection of different levels of sex steroids remains to be elucidated. In this context, an earlier report documents greater SP immunoreactivity in the medial amygdala of male compared to female rats (Micevych et al 1988), an area which is also known for a greater Kiss1 population of cells in males vs females (Stephens et al 2016). However, the interaction between these two systems (SP and Kiss1 in the medial amygdala) has not yet been explored.…”
Section: Sex Steroid Regulation Of Sp and Nkamentioning
confidence: 98%